Conformational features and binding affinities to Cripto, ALK7 and ALK4 of Nodal synthetic fragments. (15th January 2015) - Calvanese, Luisa; Sandomenico, Annamaria; Caporale, Andrea; Focà, Annalia; Focà, Giuseppina; D'Auria, Gabriella; Falcigno, Lucia; Ruvo, Menotti
Abstract : Nodal, a member of the TGF‐ β superfamily, is a potent embryonic morphogen also implicated in tumor progression. As for other TGF‐ β s, it triggers the signaling functions through the interaction with the extracellular domains of type I and type II serine/threonine kinase receptors and with the co‐receptor Cripto. Recently, we reported the molecular models of Nodal in complex with its type I receptors (ALK4 and ALK7) as well as with Cripto, as obtained by homology modeling and docking simulations. From such models, potential binding epitopes have been identified. To validate such hypotheses, a series of mutated Nodal fragments have been synthesized. These peptide analogs encompass residues 44–67 of the Nodal protein, corresponding to the pre‐helix loop and the H3 helix, and reproduce the wild‐type sequence or bear some modifications to evaluate the hot‐spot role of modified residues in the receptor binding. Here, we show the structural characterization in solution by CD and NMR of the Nodal peptides and the measurement of binding affinity toward Cripto by surface plasmon resonance. Data collected by both conformational analyses and binding measurements suggest a role for Y58 of Nodal in the recognition with Cripto and confirm that previously reported for E49 and E50. Surface plasmon resonance binding assays with recombinant proteins show that Nodal interacts in vitro also with ALK7 and ALK4 and preliminary data, generated using the Nodal synthetic fragments, suggest that Y58 of Nodal may also be involved in the recognition with these protein partners. Copyright © 2015 European Peptide Society and John Wiley & Sons, Ltd. Abstract : The structural characterization in solution of Nodal fragments, as well as the measurement of their binding affinity toward Cripto, ALK4 and ALK7 by SPR assays, is reported. Data collected by conformational analyses and binding measurements indicate a role for the Nodal E49, E50 and Y58 residues in the interaction with Cripto. For the first time, by in vitro binding assays, we find that Nodal can directly interact with ALK4. Whether this interaction has a functional relevance remains to be established.